Factors Affecting Retirement Financial Planning among Private Sector Employees in Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: With increasing life expectancy and rising living costs, retirement planning has become an important aspect of financial security for employees. In Nepal, although social security schemes such as the Employee Provident Fund (EPF), Citizen Investment Trust (CIT), and Social Security Fund exist, many private sector employees still lack adequate retirement planning. Understanding the factors that influence retirement planning behavior is therefore essential for improving financial preparedness after retirement.Purpose: The study aims to examine the factors affecting financial planning for retirement among employees working in the private sector of Kathmandu Valley.Design/Methodology/Approach: The study adopts an explanatory research design. Data was collected from 412 private sector employees using a structured self-administered questionnaire distributed through Kobo Toolbox. Both descriptive and inferential analyses were conducted using Structural Equation Modeling (SEM) with Smart PLS.Findings: The results reveal that employees with higher educational qualifications are more involved in retirement planning. Future perspective significantly influences attitude toward saving, retirement goal clarity, and retirement planning behavior. Attitude toward saving also has a significant effect on retirement planning behavior. However, social group support does not significantly influence retirement goal clarity or planning behavior. Additionally, retirement goal clarity and attitude toward saving partially mediate the relationship between future time perspective and retirement planning behavior.Conclusion: The study concludes that enhancing financial awareness and long-term financial perspectives can improve retirement planning among private sector employees. Strengthening social security programs, promoting financial education, and providing workplace retirement counseling can help employees better prepare for their post-retirement financial security.Keywords Retirement Planning, Financial Planning, Future Time Perspective, Attitude toward Saving, Retirement Goal Clarity